2007
DOI: 10.1157/13113958
|View full text |Cite
|
Sign up to set email alerts
|

Seguimiento y control de la hipertensión arterial. ¿Se efectúa igual en la población autóctona y en la inmigrante?

Abstract: The origin of the patient does not affect BP control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Aerny et al , 37 who studied the health of the immigrant population in the Community of Madrid, pointed to HBP screening below the recommended standards, especially among men (16% less); likewise, the immigrant population with shorter terms of residence made less frequent visits to the health services than did the native population. Palacios-Soler et al 38 studied the differences in the degree of control of HBP among the immigrant and native populations, and found that fewer diagnostic tests were conducted on immigrants and that the pharmacological treatment they received was inferior to that administered to the native population.…”
Section: Discussionmentioning
confidence: 99%
“…Aerny et al , 37 who studied the health of the immigrant population in the Community of Madrid, pointed to HBP screening below the recommended standards, especially among men (16% less); likewise, the immigrant population with shorter terms of residence made less frequent visits to the health services than did the native population. Palacios-Soler et al 38 studied the differences in the degree of control of HBP among the immigrant and native populations, and found that fewer diagnostic tests were conducted on immigrants and that the pharmacological treatment they received was inferior to that administered to the native population.…”
Section: Discussionmentioning
confidence: 99%